The dark Divine - Despain, Bree, 1979- (New York : Egmont USA, 2010)
Grace Divine, almost seventeen, learns a dark secret when her childhood friend--practically a brother--returns, upsetting her pastor-father and the rest of her family, around the time strange things are happening in and near their small Minnesota town.
Keywords: Interpersonal relations -- Fiction; Supernatural -- Fiction; Family life -- Minnesota -- Fiction; Christian life -- Fiction; High schools -- Fiction; Schools -- Fiction; Minnesota -- Fiction